KONDISI TERUMBU KARANG DI PESISIR KELURAHAN SUNGAI PISANG SUMATERA BARAT - Andi Yusapri; Thamrin Thamrin; Aras Mulyadi (Jurnal Ilmu Lingkungan, 2009)
uality of territorial water there are difference that is in Island of Sironjong, Island of Sirandahand Island of Pasumpahan brightness 7 metre, salinitas 30 ‰, degree of acidity (pH) 8, airtemperature 28°C and water temperature 30°C. While, in island of Sikuai brightness 5 metre,salinitas 29‰, pH 7, and water temperature 28°C. This difference is assumed by because inIsland of Sikuai stand up wisata resort and hotel. Result of coral covery of manta-tow live inIsland of Sironjong and Island of Sikuai (Coral Encrusting) with mean coral covery live equal to11 - 30% (category of II), in Island of Sirandah (Coral Heliopora) and Island of Pasumpahan(Coral Massive) with mean mount rock tutupan live equal to 31 - 50% (category of III). Resultof line transect, percentage of coral covery live at location islands research of mean in acondition heavy damage ( 0-24 %) and damage ( 25-49%). highest coral covery there are inIsland of Pasumpahan equal to 47,50% (damage) in Island of Sirandah 46,5 is% (damage), andin Island of Sikuai 23 % (heavy damage), while lowest coral covery found in Island of Sironjongequal to 15,00% (heavy damage). Mean make an index to diversity which there are in Island ofSironjong is 0,384, Island of Sirandah 0,443, Island of Sikuai 0,674 and Island of Pasumpahan0,375, ( H<1). Mean of diversity of low growth form, low spreading and low stability. Indexmean dominant coral in Island of Sironjong 0,510, In Island of Sirandah 0,705, Island of Sikuai0,737 and Island of Pasumpahan 0,644, (C come near 1) meaning there is type which dominant.